Follow-up Brucellacapt and Rose Bengal Tests in 110 Children with Brucellosis - Öcal Demir, Sevliya; Bacalan, Fatma (Journal of Pediatric Infectious Diseases, 2020)
Objective The interpretation of serologic tests in brucellosis can be difficult because of nonspecific symptoms and vague signs of disease, and limitations of serological tests to distinguish persistent and cleared infection. Here, we evaluated the role of Brucellacapt test in conjunction with Rose Bengal test (RBT) in the follow-up of children treated for brucellosis.Methods A total of 174 children diagnosed with brucellosis were included in the study. Data about demographic characteristics of patients, clinical and laboratory findings including Brucellacapt and RBT results, therapeutic approach, and response to treatment were collected from medical records.Results Of the 174 cases, 109 (62.6%) were boys and 65 (37.4%) were girls. The mean age of children at the diagnosis was 122 ± 54 months. Sixty-four cases were excluded from the study for loss to follow-up. The follow-up period for the remained 110 cases was 4.3 ± 2.9 months. Eleven cases (10%) had persistent illness, 7 (6.4%) had recurrence/relapse, and 92 had favorable outcome. During the follow-up, Brucellacapt titers did not drop under 1/320 in cases with persistent illness, and it increased again to 1/320 in cases with relapses at average 6.1 months after treatment. In 48 of cases with favorable outcome, Brucellacapt titers decreased to 1/160 in average 3.3 ± 1.8 months; in 35 cases, RBT became negative in average 3.8 ± 2.5 months, and there was no statistically significant difference between them (p = 0.241). In cases with higher Brucellacapt titers on admission, decrement of titers took longer time.Conclusion Persistent serological titers without clinical findings of brucellosis should not lead physician to prolong or repeat treatment because the decline in Brucellacapt titers and RBT negativity may be delayed in contrast to clinical recovery.
Keywords: brucellosis; Brucellacapt; Rose Bengal; children